The impact of economic sanctions on the country's economy - S. Alikhani; I. P. Khominich (Вестник университета)
Currently, sanctions are considered an important tool of international policy for maintaining security and collective response to violations of international order. At the same time, they are a factor of negative impact on the economic situation of the country, growth and production in the target country. Russia and Iran have been under sanctions from Western countries and their allies for many years and are experiencing economic problems in this regard. The article provides a characteristics and comparative analysis of economic sanctions against Russia and Iran, reveals their differences, assesses the impact of sanctions on their economic structure and financial sector. The paper shows that sanctions directly or indirectly affect the country's macroeconomic indicators and cause their decline. The authors give the substantiations for the negative impact of sanctions on the financial markets of Iran and Russia, including the banking and stock markets.